The Effect Of Durian Skin Extract (Durio zibethinus Murr.) On Histological Features Of The Lungs Rats (Rattus norvegicus) Induce 7,12-Dimetylbenz (Î‘) Anthracene (Dmba) - Syafruddin Ilyas; Jernih Nurani Hulu (International Journal of Ecophysiology, 2024)
Durian peel extract is one of the raw materials for herbal medicine that contains large amounts of flavonoids, such as flavones and flavanols, which function as antiproliferative and antioxidant. The research was conducted from September 2022 to March 2023 which aimed to analyzed the effect of durian peel extract on the morphological and histological of rat lung induced by 7.12-Dimethylbenz (Î±) Anthracene (DMBA). The samples used were 24 male rats (Rattus norvegicus) with a weight ranging from 150 to 200 grams. This method of the study used a Completely Randomized Design consisting of six treatments and four replications. Each treatment group was divided into a negative control (normal); positive control (DMBA 10 mg/kgBW); P1 (DMBA 10 mg/kgBW + methotrexate 9 mg/kgBW), P2 (DMBA 10 mg/kgBW + durian peel extract 150 mg/kgBW); P3 (DMBA 10 mg/kgBW + durian peel extract 300 mg/kgBW), and P4 (DMBA 10 mg/kgBW + durian peel extract 450 mg/kgBW). The results of this research showed that durian peel extract had significant (p<0.05) to improved the morphological damage (color, texture, weight, and volume) as well as its histology from the degeneration, inflammation, congestion, and necrosis, it was also had significant affect on the alveolar membrane, alveolar lumen and alveolar connections of the rat lung that induced by 7,12-Dimethylbenz (Î±) Anthracene (DMBA).